Peningkatan Kemampuan Problem-solving Siswa SMP pada Materi Pola Bilangan Berdasarkan Langkah-Langkah Polya - Sistyawati, Risda Intan; Sandi, Sandi; Andinasari, Andinasari (Supermat : Jurnal Pendidikan Matematika, 2024)
Mathematics is a subject that has an important role in the world of education, but not all students can solve mathematical problems well and correctly. This can be seen from the students' mathematics learning outcomes which are still low, therefore it can be said that the problem-solving process is still considered difficult by students. This research aims to design more effective learning and motivate students to learn to improve their mathematical problem-solving abilities. This type of research is called Classroom Action Research (PTK). The subjects of this research were 20 grade 8 students at one of the Junior High Schools (SMP) in Sungai Rotan District, Muara Enim Regency. This research uses test and non-test data collection techniques. The data analysis stage was carried out with quantitative data, namely from the results of the pre-test and post-test as well as the results of observations in each cycle. In this study, an assessment score of 10-100 was used. Based on the results of research conducted at one of the junior high schools where this research took place, it can be concluded that using the Polya model problem-solving learning method can improve students' mathematical problem-solving abilities.